2022
DOI: 10.1097/qai.0000000000003001
|View full text |Cite
|
Sign up to set email alerts
|

Prescribe to Save Lives: Improving Buprenorphine Prescribing Among HIV Clinicians

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…Another stepped wedge study in HIV clinics that looked at academic detailing and peer-to-peer education showed significant improvement in the confidence and readiness to prescribe buprenorphine in the 6-month postintervention phase followed by sustained improvement in the 12-month follow-up. There were no meaningful improvements in buprenorphine prescribing 13 …”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Another stepped wedge study in HIV clinics that looked at academic detailing and peer-to-peer education showed significant improvement in the confidence and readiness to prescribe buprenorphine in the 6-month postintervention phase followed by sustained improvement in the 12-month follow-up. There were no meaningful improvements in buprenorphine prescribing 13 …”
Section: Discussionmentioning
confidence: 91%
“…There were no meaningful improvements in buprenorphine prescribing. 13 Further research should focus on understanding the barriers to preferring onsite treatment. Our baseline formative evaluation identified difficulty with determining treatment eligible patients, variable experiences with prior medications for addiction treatment, perceived complexity of treatments, perceived need for robust behavioral services, and inconsistency in availability of trained onsite specialists as barriers.…”
Section: Discussionmentioning
confidence: 99%